A global two-temperature corona and inner heliosphere model: A comprehensive validation study - Jin, M. (2012)
The recent solar minimum with very low activity provides us a unique opportunity for validating solar wind models. During CR2077 (2008 November 20 through December 17), the number of sunspots was near the absolute minimum of solar cycle 23. For this solar rotation, we perform a multi-spacecraft validation study for the recently developed three-dimensional, two-temperature, Alfvén-wave-driven global solar wind model (a component within the Space Weather Modeling Framework). By using in situ observations from the Solar Terrestrial Relations Observatory (STEREO) A and B, Advanced Composition Explorer (ACE), and Venus Express, we compare the observed proton state (density, temperature, and velocity) and magnetic field of the heliosphere with that predicted by the model. Near the Sun, we validate the numerical model with the electron density obtained from the solar rotational tomography of Solar and Heliospheric Observatory/Large Angle and Spectrometric Coronagraph C2 data in the range of 2.4 to 6 solar radii. Electron temperature and density are determined from differential emission measure tomography (DEMT) of STEREO A and B Extreme Ultraviolet Imager data in the range of 1.035 to 1.225 solar radii. The electron density and temperature derived from the Hinode/Extreme Ultraviolet Imaging Spectrometer data are also used to compare with the DEMT as well as the model output. Moreover, for the first time, we compare ionic charge states of carbon, oxygen, silicon, and iron observed in situ with the ACE/Solar Wind Ion Composition Spectrometer with those predicted by our model. The validation results suggest that most of the model outputs for CR2077 can fit the observations very well. Based on this encouraging result, we therefore expect great improvement for the future modeling of coronal mass ejections (CMEs) and CME-driven shocks. © 2012. The American Astronomical Society. All rights reserved.